مفهوم "البَرَكَات" من قوله تعالى :{ لفتحنا عليهم بركات} عند اللغويين ومعانيها باللغة الماليزية - Zulkipli Bin Md. Isa; Hj. Sulaiman Bin Ismail; Lubna Abd Rahman; Nurhasma Bt. Muhamad Saad; Wahida Bt.Mansor; Muhammad Marwan Ismail (USIM Press, 2024)
VOL. 28,2023 Page (102-113 )